s̃βs- Open Sets and s̃βs- Continuous in Soft Topological Spaces - Ahmed, Nehmat K.; Mohammed, Shaymaa M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Our work introduces the notion of  -open set. This class of - open sets is not directly comparable to the categories of soft open, -closed. We demonstrate that the category of  -open sets lies strictly between the class of -open sets and -open sets. Additionally, we investigate the connections that exist between -open sets along with other kinds of soft sets. Moreover, we provide several criteria that are sufficient for determining the equivalence between -open sets and every one of -open sets and -open sets. Also, according to our findings, the family of -open sets is a supra soft topology. Furthermore, we make it clear the correlation that exists between the respective categories of  -open sets in a soft topological space and in its soft topological subspace. Finally, the class of -continuous function is introduced, it is main properties are studied and derive some of the properties of these soft functions under the soft composition of soft functions.